Coessential-connection by microwave plasma chemical vapor deposition: a common process towards wafer scale single crystal diamond. Issue 1 (2nd January 2021) - Shu, Guoyang; Dai, Bing; Bolshakov, Andrey; Wang, Weihua; Wang, Yang; Liu, Kang; Zhao, Jiwen; Han, Jiecai; Zhu, Jiaqi
Abstract: Large size single crystal diamond (SCD) wafer has been strongly desired for various of advanced applications, while two major potential approaches, including mosaic growth and heteroepitaxy based on chemical vapor deposition method, are both stuck with respective technical barriers. This paper reveals and summarizes the essential commonality of the two schemes, and denominates the concept of "coessential-connection" (CC) growth. Such generalized concept involved the nature of the single crystal and polycrystalline diamond film deposition with similar mechanism and processes. The principle of CC growth process with detailed classification was elaborated, and influence of nucleus size and orientation mismatch was clarified, which is regarded as the core problem of large area SCD film growth via coessential-connection process.